A survey study on environmental consciousness in Famagusta - Asilsoy, Buket (Elsevier Science Bv, 2012)
Today many cities are considered unsustainable owing to mainly the pressures of industrial development, technological improvements, and concentration of populations. On that ground, the concept of sustainability has emerged as a new way of thinking. Nevertheless, it has recently been recognized that urban residents with environmentally conscious attitudes, behaviours and habits is another important aspect to fulfill the requirements for sustainable urbanism. Within these objectives, a framework for the research will be described in the article. After briefly achieving an understanding of 'sustainable urbanism', environmental attitudes, everyday practices and behaviours will be conceptualized. Than the research objectives will be highlighted. (C) 2012 Published by Elsevier B.V. Selection and/or peer-review under responsibility of Centre for Environment-Behaviour Studies(cE-Bs), Faculty of Architecture, Planning & Surveying, Universiti Teknologi MARA, Malaysia
Asia Pacific International Conference on Environment-Behaviour Studies (AicE-Bs) -- DEC 07-09, 2011 -- Eastern Mediterranean Univ (EMU), Urban Res & Dev Ctr (URDC), Famagusta, CYPRUS
Keywords: Sustainable urbanism; environmental behaviour; everyday household practices; Famagusta